Exploring adventure-based tourism digitization for effective marketing strategies / Mohd Shariman Shafie … [et al.] - Shafie, Mohd Shariman; Abdul Rasid, Aida Roha; Ab Aziz, Mohd Noorazlan; Hashim, Mustakim; M. Antara, Purnomo; Shafie, Nur Amalina; Mohd Beta, Raja Mayang Delima (2023)
This research study aims to explore the role of digitization in enhancing marketing strategies in the adventure-based tourism industry. With the increasing importance of digital technologies and platforms, understanding their impact on marketing effectiveness becomes crucial for businesses operating in this sector. By conducting a comprehensive literature review and employing a mixed-methods approach, this research seeks to examine the current state of adventure-based tourism digitization, identify effective digital marketing strategies, and provide valuable insights and recommendations. The findings of this study will contribute to the existing knowledge base and assist adventure-based tourism businesses in developing effective and sustainable marketing strategies in the digital era. Adventure-based tourism has gained popularity as travelers seek unique and thrilling experiences. In this digital age, harnessing the power of digitization for marketing is crucial in promoting adventure-based tourism destinations and services. This research paper employs a bibliometric analysis approach to explore the existing body of literature on adventure-based tourism digitization and its implications for effective marketing strategies. By systematically reviewing and analyzing academic articles, this study identifies trends, gaps, and emerging themes in the literature, offering valuable insights for tourism practitioners, policymakers, and researchers.